INFLUENCE OF PUBLIC OPINION ON THE MANAGEMENT OF VACCINE ISSUES - Juan Malik Frederick Turpyn; Manik Sunuantari (EKSPRESI DAN PERSEPSI : JURNAL ILMU KOMUNIKASI, 2022)
The issue of vaccines circulating in the community is identical to the vaccination process, or the vaccine itself. Such as the issue of the corona-vac vaccine that is not effective against the virus, to the Moderna vaccine which is said to have harmful vaccine effects if injected. This makes the role of the government, legislators, and the community synergize to be able to set the record straight on the issue of vaccines. One of them is The government of DKI Jakarta tries to restore what issues spread to the public. The approach used in this study is quantitative, as the research is presented with figures statistically to convey circumstances that correspond to the facts in the field about public opinion and vaccine issues. Based on the results obtained in this study, it can be concluded that public opinion influences the management of issues with a positive relationship direction. Based on the results obtained in this study, it can be concluded that public opinion influences the management of issues with a positive relationship direction and strong strength. Because basically this concept of public opinion serves as a public step to find out what the conditions are like with the issues circulating today.